Rapid detection of ethanol in beverages using IIUM-fabricated electronic nose - Nurul Asyikeen A.M.; Jaswir I.; Akmeliawati R.; Ibrahim A.M.; Aslam M.; Octavianti F. (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS